2010
DOI: 10.1088/0964-1726/19/11/115027
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of a self-powered smart damping system in reducing vibrations of a full-scale stay cable

Abstract: This paper investigates the effectiveness of a self-powered smart damping system consisting of a magnetorheological (MR) damper and an electromagnetic induction (EMI) device in reducing cable vibrations. The proposed smart damping system incorporates an EMI device, which is capable of converting vibration energy into useful electrical energy. Thus, the incorporated EMI device can be used as an alternative power source for the MR damper, making it a self-powering system. The primary goal of this experimental st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Figures 14 and 15 compare the additional first two modal damping ratios provided by a single ECIMD and two ECIMDs at the same end, respectively. In test cases (Cases 3,4,6,7,9,(10)(11)(12)(13)(15)(16)(17)(18)(19)22,24,25,(28)(29)(30)(31)(34)(35)(36)(37) from Figure 14 and all cases from Figure 15, the additional modal damping ratios provided by both the ECIMD 1 and ECIMD 2 are less than those provided by a single ECIMD 2 . In test cases (Cases 2,5,8,14,20,21,23,26,27,32,and 33) from Figure 14, the additional first modal damping ratios provided by both the ECIMD 1 and ECIMD 2 on the same cable end are larger than those provided by a single ECIMD 2 .…”
Section: Two Ecimds At the Same Cable Endmentioning
confidence: 97%
See 2 more Smart Citations
“…Figures 14 and 15 compare the additional first two modal damping ratios provided by a single ECIMD and two ECIMDs at the same end, respectively. In test cases (Cases 3,4,6,7,9,(10)(11)(12)(13)(15)(16)(17)(18)(19)22,24,25,(28)(29)(30)(31)(34)(35)(36)(37) from Figure 14 and all cases from Figure 15, the additional modal damping ratios provided by both the ECIMD 1 and ECIMD 2 are less than those provided by a single ECIMD 2 . In test cases (Cases 2,5,8,14,20,21,23,26,27,32,and 33) from Figure 14, the additional first modal damping ratios provided by both the ECIMD 1 and ECIMD 2 on the same cable end are larger than those provided by a single ECIMD 2 .…”
Section: Two Ecimds At the Same Cable Endmentioning
confidence: 97%
“…It has been found that the semi‐active MR dampers can provide much higher additional damping for stay cables than passive VDs 13,14 and can also achieve better control performance for multimode cable vibrations because of their negative stiffness characteristics 15–17 . Nevertheless, semi‐active control still requires a stable external power supply, a sensing system, and a controller, which hinders wide applications due to its complexity and diseconomy 18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Suda et al (2004) designed an energy recycling system using an electromagnet (EM) as the vibration-absorber. Several other researchers developed energy harvesters for cars including the one by Choi and Wereley (2009), which comprises a rotor, permanent magnet, and a MR damper, a smart EM harvester by Kim et al (2010), and a piezoelectric harvester by Xiao et al (2015). One drawback of the aforementioned energy harvesters is that they require complicated feedback control.…”
Section: Introductionmentioning
confidence: 99%
“…MRF is most commonly used in dampers, especially in (a) the primary suspension systems of vehicles [ 8 , 9 , 10 , 11 , 12 , 13 ], (b) the secondary suspension of driver seats in trucks [ 14 , 15 , 16 , 17 , 18 ], (c) the damping of vibration for seismic activity protection [ 19 , 20 , 21 , 22 ], or (d) the damping of cable bridge vibrations caused by wind and rain [ 23 , 24 ]. Semi-active control can be easily applied to magnetorheological (MR) dampers.…”
Section: Introductionmentioning
confidence: 99%